Compensatory Incentives for Performance Improvement in University Corporate Governance; [Incentivos Compensatorios Para Mejorar Desempeño en Los Gobiernos Corporativos Universitarios] - Abello-Romero, J (Asociacion Nacional de Universidad e Instituciones de Educacion Superior, 2023)
The article evaluates the Ibero-American academic community’s assessment of intrinsic and extrinsic compensatory incentives to improve the performance of members of University Corporate Governments (ucg). A survey applied to members of Ibero-American universities is analyzed. Their mean ratings are described through the use of violin diagrams, and differences in the ratings of different groups are analyzed using a nonparametric test. Since differences were found between groups of experts, standardized incentives for ucg members should be avoided. The study’s implication indicates that the results should be taken into account to establish compensatory incentives that allow for a better performance of the ucgs. © 2016 Asociación Nacional de Universidades e Instituciones de Educación Superior A.C. Este es.